Proteomic investigation of Sri Lankan hump-nosed pit viper (Hypnale hypnale) venom. (January 2015) - Tan, Choo Hock; Tan, Nget Hong; Sim, Si Mui; Fung, Shin Yee; Gnanathasan, Christeine Ariaranee
Abstract: The hump-nosed pit viper, Hypanle hypnale, contributes to snakebite mortality and morbidity in Sri Lanka. Studies showed that the venom is hemotoxic and nephrotoxic, with some biochemical and antigenic properties similar to the venom of Calloselasma rhodostoma (Malayan pit viper). To further characterize the complexity composition of the venom, we investigated the proteome of a pooled venom sample from >10 Sri Lankan H. hypnale with reverse-phase high performance liquid chromatography (rp-HPLC), sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) and peptide sequencing (tandem mass-spectrometry and/or N-terminal sequencing). The findings ascertained that two phospholipase A2 subtypes (E6-PLA2, W6-PLA2 ) dominate the toxin composition by 40.1%, followed by snake venom metalloproteases (36.9%), l -amino acid oxidase (11.9%), C-type lectins (5.5%), serine proteases (3.3%) and others (2.3%). The presence of the major toxins correlates with the venom's major pathogenic effects, indicating these to be the principal target toxins for antivenom neutralization. This study supports the previous finding of PLA2 dominance in the venom but diverges from the view that H. hypnale venom has low expression of large enzymatic toxins. The knowledge of the composition and abundance of toxins is essential to elucidate the pathophysiology of H. hypnale envenomation and to optimize antivenom formulation in the future. Graphical abstract: Highlights: Venom pooled from multiple Hypnale hypnale was characterized for proteome. The major toxin types and composition abundance were ascertained. E6-and W6-PLA2 dominate the venom proteome much as 40%. Large enzymatic toxins e.g. LAAO, SVMP form another large bulk (>50%) of the venom. Toxin abundances reflect their pathogenic roles and suggest targets for antivenom.